Immunostimulatory activity of brown seaweed-derived fucoidans at different molecular weights and purity levels towards white spot syndrome virus (WSSV) in shrimp Litopenaeus vannamei - Ellya Sinurat & , Endang Saepudin, Rosmawaty peranginangin, Sumi Hudiyono (Journal of Applied Pharmaceutical Science, 2016)
Fucoidan used as immunostimulant is commonly in the crude form. In this study, we investigated the effect of fucoidan in both crude and purified forms in their immunostimulatory activity. In addition, we studied the effect of low- and high-molecular weight fucoidan as hydrolysis products toward immunostimulatory activity. Four kinds of fucoidan were assayed for immunostimulant activity on the shrimp Litopenaeus vannamei. The parameters observed in the assay includes the mortality number, haemocyte, gene-related immunity (phenoloxidase, superoxide dismutase and transglutaminase) in the shrimps infected with viral WSSV. The assay results showed that pure fucoidan exhibited higher activity compared with that of crude fucoidan. Sulfate and carbohydrate content of HMW fucoidan are 7.8 % and 82.54 % with an estimated molecular weight of 8.28 x104 Dalton, and low molecular weight (LMW) fucoidan has 1.2% and 65.23% with an estimated molecular weight of 7.53 x104 Dalton. The transcriptional level of the immunity-related genes was found higher after feeding the infected shrimps with purified and HMW fucoidan. In particular, all of fucoidan forms increased the phenoloxidase gene transcription, suggesting that fucoidan have significant role in the production of phenoloxidase.
Keywords: Fucoidan, Immunostimulant, WSSV, Molecule weight, Shrimp.